Schizophrenia: do men and women suffer from the same disease? (Archives of Clinical Psychiatry, 2002)
This article reviews the literature on normal brain development and behavioural development in men and women as well as on aetiological risk factors for schizophrenia, such as pre-, peri- and postnatal complications. The male-female comparisons of age and type of onset, symptomatology, course and outcome were based on a population-based sample of 232 first illness episodes - the ABC Schizophrenia Study sample. The probands were assessed using the IRAOS interview and other instruments retrospectively at first admission and prospectively at six cross sections over five years after first contact. A representative subsample of 130 first admissions or 115 first illness episodes were compared with 130 controls, matched by age, sex and area of residence. Women, 3 to 4 years older than men at illness onset, showed a second peak of onsets in age group 45 to 50 years. After animal experiments and a controlled clinical study this finding was explained by a protective effect of oestrogen persisting until menopause. The underlying neurobiological mechanism consisted in a sensitivity reducing effect of oestrogen on D2 receptors in the brain. The effect of oestrogen, meanwhile confirmed in randomised control trials, also includes genomic effects as well as interactions with free-radical detoxifying systems, thus demonstrating the neuroprotective capabilities of oestrogen. Postmenopausal schizophrenia was more frequent and more severe in women. Men fell ill more frequently and more severely at young age and less frequently and more mildly later in life. Illness course, too, was more unfavourable in postmenopausal women than in their male peers. The protective effect of oestrogen in women depended on the degree of their predisposition to the illness: the higher the familial load for schizophrenia, the weaker the protection by oestrogen. The more favourable illness course in premenopausal women resulted from their higher level of social development at illness onset - determined by their higher age at onset - and from their socially more adaptive behaviour. The illness behaviour of young men showed a significant excess of socially negative behaviours with an unfavourable impact on their early illness course. In contrast, older men were socially better adjusted. With genetic and morphological findings considered the subtypes of schizophrenia did not differ between men and women. Gender differences in symptomatology and course of schizophrenia obviously are not explained by differences in the disease process. They seem to be determined by a complex pattern of interaction between disease variables, hormonal and behavioural differences and their consequences for age at onset and illness course.